Peran Manajerial Kepala Sekolah Dalam Menanamkan Nilai Cinta Kasih DI SD Negeri 1 Gergunung - Imelda Oktavia Wibowo; Dzulfikar Aziz Munandar; Celsi Julia Andini; Melati Puspita Saputri Aryani; Theresia Winda Setyaningrum; Maria Melani Ika Susanti (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
The managerial role of the school principal plays an essential part in leading the sustainability of the school to achieve its educational goals. However, there are still many school principals who have not fully implemented the appropriate actions to achieve these goals, especially in terms of instilling character values that emphasize moral and ethical principles, such as the value of love and affection.This study aims to describe the managerial role of the school principal in instilling the value of love and affection in elementary school settings. The value of love and affection is crucial as a foundation for the development of students' character, which not only plays a role in academic achievements but also in shaping behaviors that are ethical and moral in society. This research uses a descriptive qualitative approach with data collection techniques through observation and in-depth interviews. The subjects of the research include the school principal and several teachers involved directly in the implementation of the school programs. Data analysis is conducted using an interactive model, which includes data collection, data reduction, data presentation, and conclusion drawing. The findings of the study indicate that the school principal plays a very strategic role in shaping a culture of love and affection through leadership that sets an example, strengthening communication among school members, as well as implementing school programs such as BERKAH (rice charity), murojaah, art exhibition, and camping activities. These programs not only strengthen relationships among students but also foster a sense of empathy and solidarity in daily life within the school environment.